GMRT 610 MHz observations of galaxy clusters in the ACT equatorial sample. Issue 1 (27th March 2019) - Knowles, Kenda; Baker, Andrew J; Bond, J Richard; Gallardo, Patricio A; Gupta, Neeraj; Hilton, Matt; Hughes, John P; Intema, Huib; López-Caraballo, Carlos H; Moodley, Kavilan; Schmitt, Benjamin L; Sievers, Jonathan; et al.
Abstract: We present Giant Metrewave Radio Telescope (GMRT) 610 MHz observations of 14 Atacama Cosmology Telescope (ACT) clusters, including new data for nine. The sample includes 73 per cent of ACT equatorial clusters with M 500 > 5 × 10 14  M⊙ . We detect diffuse emission in three of these (27$^{+20}_{-14}$  per cent): we detect a radio minihalo in ACT-CL J0022.2–0036 at z  = 0.8, making it the highest redshift minihalo known; we detect potential radio relic emission in ACT-CL J0014.9–0057 ( z  = 0.533); and we confirm the presence of a radio halo in low-mass cluster ACT-CL J0256.5+0006, with flux density S 610  = 6.3 ± 0.4 mJy. We also detect residual diffuse emission in ACT-CL J0045.9–0152 ( z  = 0.545), which we cannot conclusively classify. For systems lacking diffuse radio emission, we determine radio halo upper limits in two ways and find via survival analysis that these limits do not significantly affect radio power scaling relations. Several clusters with no diffuse emission detection are known or suspected mergers, based on archival X-ray and/or optical measures; given the limited sensitivity of our observations, deeper observations of these disturbed systems are required in order to rule out the presence of diffuse emission consistent with known scaling relations. In parallel with our diffuse emission results, we present catalogues of individual radio sources, including a few interesting extended sources. Our study represents the first step towards probing the occurrence of diffuse emission in high-redshift ( z  ≳ 0.5) clusters, and serves as a pilot for statistical studies of larger cluster samples with the new radio telescopes available in the pre-SKA era.